2011
DOI: 10.1007/s00442-011-2142-6
|View full text |Cite
|
Sign up to set email alerts
|

Linking landscape history and dispersal traits in grassland plant communities

Abstract: Dispersal limitation and long-term persistence are known to delay plant species' responses to habitat fragmentation, but it is still unclear to what extent landscape history may explain the distribution of dispersal traits in present-day plant communities. We used quantitative data on long-distance seed dispersal potential by wind and grazing cattle (epi- and endozoochory), and on persistence (adult plant longevity and seed bank persistence) to quantify the linkages between dispersal and persistence traits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 55 publications
6
78
4
Order By: Relevance
“…In the present research, both taxonomic and phylogenetic alpha diversity increased during succession. This is consistent with previous studies which found that taxonomic and phylogenetic diversity increased with successional age either in forest4665 or in herbaceous plant communities20. Interesting, we also found that although the phylogenetic alpha diversity significantly increased with succession, communities of later stages became more phylogenetic clustering.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present research, both taxonomic and phylogenetic alpha diversity increased during succession. This is consistent with previous studies which found that taxonomic and phylogenetic diversity increased with successional age either in forest4665 or in herbaceous plant communities20. Interesting, we also found that although the phylogenetic alpha diversity significantly increased with succession, communities of later stages became more phylogenetic clustering.…”
Section: Discussionsupporting
confidence: 93%
“…To be able to predict ecosystem responses to future disturbance events and environmental changes, we need a better understanding of the processes that govern community assembly, and thus generate biodiversity, during succession19. Theory predicts that, as succession proceeds, the relative importance of abiotic and biotic filtering processes is likely to change20. Species in newly opened areas experience environmental adversity, thus environmental and dispersal filtering are likely to structure early stage development21.…”
mentioning
confidence: 99%
“…Surprisingly, we found no significant evidence of trait convergence at the landscape scale. This lack of convergence suggests that at the landscape scale, the effects of stochastic processes linked to dispersal limitation and landscape structure were more important than effects due to differences in environmental conditions between patches (Purschke et al 2012). In contrast, trait-based species sorting was detectable within a grassland patch, where dispersal limitation can be considered to be negligible.…”
Section: A S S E M B L Y a T B R O A D E R S P A T I A L S C A L E Smentioning
confidence: 80%
“…However, Grime (2006) further predicted that when disturbance (grazing in the present study) ceases, increased competition and competitive exclusion of less competitive species would lead to trait convergence -a prediction not confirmed in our analyses. On the one hand, such competitive exclusion is likely to take time in perennial communities where plant individuals may persist for decades under unfavourable conditions (Helm, Hanski & P€ artel 2006;Purschke et al 2012). In the abandoned grasslands of our study, grazing ceased c. 5-10 years ago and that time period may have been too short to allow turnover of individual plants and the detection of competitive exclusion.…”
Section: I S T U R B a N C E E F F E C T Smentioning
confidence: 83%
“…If species diversity in cultivated landscapes is to be maintained and enriched in the future, species will need to be able to disperse from old, species-rich grassland fragments into younger grasslands [10]. Optimization of the spatial distribution of grassland fragments will require information that discriminates between land cover belonging to different stages in the succession from arable fields to old semi-natural grasslands.…”
Section: Introductionmentioning
confidence: 99%